2019
DOI: 10.1136/bmjgh-2018-001141
|View full text |Cite
|
Sign up to set email alerts
|

The role of community health workers in addressing the global burden of ear disease and hearing loss: a systematic scoping review of the literature

Abstract: IntroductionCommunity health workers (CHWs) have the potential to improve access to ear and hearing services for people across low-income or middle-income countries, remote, underserved, or resource-poor areas of the world. We performed a systematic scoping review to identify evidence on how CHWs are currently deployed in the prevention, screening, diagnosis, treatment and management of ear disease and hearing loss; methods to train and support CHWs in this context; and cost-effectiveness of CHWs.MethodsWe per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 75 publications
(192 reference statements)
2
54
0
4
Order By: Relevance
“…These manuals have been used in several countries to train community health workers, including Brazil, Burkina Faso, China, Colombia, Fiji, Kenya, Malawi and Nigeria. 16 Other regional or national resources for training community health workers are available, for example the Aboriginal and Torres Strait Islander ear health manual 17 from Australia, and the Chinese ear and hearing care training manual. 18 Training programmes to date have reported learner outcomes of community health workers in terms of short-term improvements in knowledge, 16 rather than ability to independently assess or manage ear and hearing disorders.…”
Section: Primary-care Assessment and Interventionmentioning
confidence: 99%
See 3 more Smart Citations
“…These manuals have been used in several countries to train community health workers, including Brazil, Burkina Faso, China, Colombia, Fiji, Kenya, Malawi and Nigeria. 16 Other regional or national resources for training community health workers are available, for example the Aboriginal and Torres Strait Islander ear health manual 17 from Australia, and the Chinese ear and hearing care training manual. 18 Training programmes to date have reported learner outcomes of community health workers in terms of short-term improvements in knowledge, 16 rather than ability to independently assess or manage ear and hearing disorders.…”
Section: Primary-care Assessment and Interventionmentioning
confidence: 99%
“…Other studies suggest that community health workers can acquire sufficient practical skills to assess and manage patients. 16 Community health workers in India were able to perform a whispered voice test to screen for hear-ing loss in adults, 19 and in Malawi they could identify patients with potential hearing problems. 20 Several studies have shown that community health workers are able to capture images on digital otoscopy.…”
Section: Primary-care Assessment and Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The worldwide weight of crippling hearing misfortune is most extreme (80%) in those living in low-salary or center pay nations (LMICs). Additionally there is a de iciency of expert ear care experts in LMICs, so the job of network arranged ear care arrangement at PHC level become crucial [3]. CHWs at PHC level can assume a major job in improving access to ear and hearing administrations, for example, screening and raising network awareness [3].…”
Section: Worldwide Scenario Of Hearing Lossmentioning
confidence: 99%